Outcome of a dentigerous cyst following decompression using a removable appliance: a case report - (:unkn) unknown (My University, 2014)
A dentigerous cyst is a benign odontogenic cyst that is associated with the crown of an unerupted permanent tooth. This report describes a conservative approach to treatment using a customised removable appliance for managing a large dentigerous cyst in a 7-year-old female. At the 2-year follow-up, healing of the lesion and ossification of the bony defect was observed.